The secret life of young adolescents living with HIV in northern Mozambique - a mixed methods study - Joana Falcão; Allison Zerbe; Claude Ann Mellins; Joanne Mantell; Kirsty Brittain; Bill Kapogiannis; Eduarda Pimentel de Gusmao; Teresa Beatriz Simione; Elaine J. Abrams (BMC, 2021)
Abstract Background In Mozambique, HIV infection remains a leading cause of adolescent mortality. With advances in antiretroviral treatment (ART), the population of adolescents living with vertically-acquired HIV is growing. Most studies of adolescents living with HIV (ALHIV) focus on older youth with horizontal infection. As part of a larger study, we examined the characteristics and health care needs of younger ALHIV, including those with vertically-acquired infection to inform preventive interventions. Methods We used a convergent mixed-methods design and recruited ALHIV aged 12-14 years who were enrolled in HIV care in three health clinics in Nampula, Mozambique. From 11/2019-3/2020, we conducted 61 quantitative surveys and 14 in-depth interviews with a purposively selected subset of ALHIV who were aware of their HIV status. Descriptive statistical analysis was conducted for quantitative data. Qualitative data were transcribed and analyzed using thematic analysis. Results The median age of ALHIV was 13 years, 50% were female, 67% lived with ≥1 parent, 70% had lost a parent, 100% were in school; 10% were in a relationship, and 3% had initiated sexual activity. Among 31 ALHIV aware of their serostatus, the median age of antiretroviral treatment (ART) initiation was 8 years (IQR: 6-11); 55% received caregiver support for ART management; 35% reported missing ≥1 ART dose in the last 30 days; 6% had disclosed their HIV-status to friends and 48% reported no one to talk to about HIV-specific issues. Four main themes emerged from the qualitative interviews with ALHIV: a) learning one's HIV-positive status as the beginning of a secret life; b) importance of caregivers' support for ART management; c) high value of ALHIV peer support to overcome isolation, increase HIV literacy, and support adherence; and d) unmet needs for sexual and reproductive health education. Conclusion HIV-related secrecy prevails among ALHIV, a situation exacerbated by caregivers and healthcare providers. Caregivers play a major role in supporting adherence among young ALHIV, yet ALHIV could also benefit from adolescent-friendly services, including peer support, sexual and reproductive health services and preparation for independent health management. Integrating such programs into ART services in Mozambique may be critical to promoting ALHIV health.